Trends in hydrological models integrated with geographical information systems by scientometric - Caetano, Jordana Moura; Casaroli, Derblai (Comunicata Scientiae, 2016)
The remote sensing and Geographic Information Systems (GIS) development have encouraged and improved the use and spansion of hydrological models worldwide. This development allows the use of hydrological models, simulating watersheds systems operation in a more simple, economical and realistic way. In order to maximize this integration, new computational tools, hydrological models and GIS are being developed. This study aimed to apply the scientometric study to quantify and verify the tendencies of the scientific publications of hydrological models and their integration with geographic information systems (GIS). Scientific papers search was accomplished in Scopus database, using the following terms: modeling OR model* AND hydrologic* OR hidrological AND “Geographic* Information* System*” OR “GIS”, and the data were obtained on September 21, 2015. It can be observed, in general, an increase in the number of papers published according to time, in years (r = 0.96) and the same trend was observed for Brazilian studies, starting from 2006. Moreover, the main direction of these studies is to develop methodologies that could integrate hydrological models with GIS.